Pengaruh Likuiditas dan Profitabilitas terhadap Nilai Perusahaan dengan Keputusan Pendanaan sebagai Variabel Moderasi pada Perusahaan Subsektor Tekstil dan Garmen yang Terdaftar di BEI Periode 2016-2020 - Marcelina Marcelina; Evaliati Amaniyah (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
Business competition requires companies to survive and achieve the company's goals, namely the prosperity of shareholders by increasing share prices which are reflected through company value. The purpose of this study was to determine the effect of liquidity and profitability on firm value with funding decisions as a moderating variable in textile and garment sub-sector companies listed on the Indonesian stock exchange for the 2016-2020 period. Of the 21 companies, purposive sampling method was used so that the remaining 16 companies were used as research samples. The variables used are liquidity and profitability as independent variables, firm value as the dependent variable, funding decisions as moderating variables. Tests using the moderated regression analysis technique show that: (1) Liquidity has a significant positive effect on firm value (2) Profitability has a non-significant positive effect on firm value (3) Funding decisions are unable to moderate the effect of liquidity on firm value (4) Funding decisions are able to moderate the effect of profitability on firm value.